PROBING INTO THE DIGITAL PERFORMING ARTS PROGRAM : A NEEDS ANALYSIS - Wuryani Hartanto (LINGUAMEDIA Journal, 2025)
This study dealt with Digital Performing Arts, henceforth called DPA, a relatively new program affiliated with The Faculty of Language and Arts. Being a part of the faculty, DPA includes English language skills, such as Speaking, Listening, Reading and Writing courses in their curriculum to equip the students with the abilities to communicate in English. It is expected that during the course of their study at DPA, students do not only learn to use English, but also produce qualified, prestigious performing art works in English, probably even their masterpieces to be introduced worldwidely. Bearing this in mind, the present researcher conducted this study which aimed at revealing the opinions of the students about the DPA program. Hence, the research problems can be formulated as follows. Firstly, what are the students views on the concept and goals of DPA program? Secondly, what are the students views on the subjects offered in DPA curriculum? and Lastly, what are the students’ suggestions for the improvement of DPA program? The respondents of this study were 23 active DPA students from 2020 to 2024 batches and 2 alumni. This study was designed to use the quantitative method and the instrument was questionnaire. The results of the questionnaire were analyzed using SPPS 25 and some were calculated on a percentage basis. The research findings indicate that the majority of the students are satisfied with the concept and goals of DPA program even though they suggest that some irrelevant subjects in DPA curriculum need revising.